Diatomic metal electrocatalyst as well as preparation method and application thereof
By adsorbing and heat-treating metal chloride dimers on nitrogen-doped carbon materials, an efficient diatomic metal electrocatalyst was prepared, which solved the problem of inconvenient synthesis of diatomic catalysts in the prior art and achieved high catalytic activity and stability oxygen reduction reaction.
Patent Information
- Application Number
- CN202310962287.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-02
AI Technical Summary
The lack of simple, precise and controllable synthesis strategies in the prior art to prepare diatomic catalysts, resulting in limited catalytic efficiency and stability of the catalyst.
By sublimating the metal chloride dimers within a certain temperature range using anhydrous iron chloride or anhydrous aluminum chloride, it is adsorbed onto nitrogen-doped carbon materials, and a high proportion, uniformly loaded diatoms are obtained after heat treatment. Metal electrocatalyst.
A diatomic metal electrocatalyst with high diatomic site density and good dispersion is achieved, which significantly improves the catalytic activity and selectivity of the oxygen reduction reaction, and has high stability.
Smart Images

Figure CN119433590A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrocatalysis, and in particular relates to a diatomic metal electrocatalyst and a preparation method and application thereof. Background Art
[0002] Single-atom catalysts have been shown to have improved catalytic activity, selectivity and stability in various reactions due to their nearly 100% atomic utilization, unsaturated coordination environment and unique electronic structure. However, the linear proportional relationship between the adsorption strengths of different reaction intermediates on the single atom active site is difficult to break, which limits the improvement of its catalytic efficiency. In addition, single-atom catalysts usually use low metal loading to prevent aggregation, which also largely limits their practical application. Diatomic catalysts with adjacent dimetallic atomic sites are regarded as an extension of single-atom catalysts and provide a feasible strategy to solve the above problems. On the basis of maintaining the advantages of single-atom catalysts, diatomic catalysts show a more flexible active site structure and are expected to achieve higher metal loading. Diatomic catalysts provide adjacent metal atom active sites for complex catalytic reactions (such as electrocatalytic oxygen reduction reactions), which can realize multiple binding modes of reactant / intermediate molecules and simultaneous binding of different molecules, increasing the possibility of reaction paths. In addition, the synergistic effect between diatoms can effectively regulate the electronic interaction between reactants / intermediates and active sites. These characteristics give diatomic catalysts the opportunity to break the linear proportional relationship of intermediate adsorption strength, thereby achieving improved catalytic activity and selectivity.
[0003] In recent years, diatomic catalysts have made some breakthroughs in the field of catalysis and have become a hot research direction in nanocatalysis chemistry. However, there is still a lack of simple, precise and controllable synthetic strategies to prepare diatomic catalysts. High-temperature pyrolysis is a relatively simple and commonly used method, but it is usually carried out at above 800°C, which will cause the aggregation of some metal atoms, thus affecting the catalytic performance. Although some deposition techniques can effectively control the synthesis process, it is difficult to avoid the coexistence of a large number of single-atom sites, and the equipment requirements are high, and the test conditions need to be strictly controlled. In recent years, wet chemical synthesis methods have also become the focus of research by scientific researchers, but this method usually uses low concentrations of metal precursors to ensure good atomic dispersion. In addition, the weak interaction between the metal center and the carrier is another problem of this method, which will affect the catalytic efficiency of the final catalyst.
[0004] Therefore, it is of great value and significance to develop a simple, easy-to-obtain, high-catalytic-performance diatomic catalyst with high diatomic site density and good dispersion.
[0005] In order to solve the above problems, the present invention is proposed. Summary of the invention
[0006] In view of the problems existing in the background technology, the purpose of the present invention is to provide a diatomic metal electrocatalyst and its preparation method and application. The preparation method is based on the physical property that anhydrous ferric chloride and anhydrous aluminum chloride sublimate into metal chloride dimers within a certain temperature range, and uses nitrogen-doped carbon materials as conductive substrates. After adsorption, heat treatment and other steps, a diatomic metal electrocatalyst uniformly loaded on nitrogen-doped carbon materials is obtained. The prepared catalyst can be applied to electrocatalytic oxygen reduction reactions.
[0007] The first aspect of the present invention provides a diatomic metal electrocatalyst, the diatomic metal electrocatalyst comprising: a conductive substrate, diatomic iron or diatomic aluminum loaded on the conductive substrate, the diatomic iron being two iron single atoms, the diatomic aluminum being two aluminum single atoms, and the distance between the two iron single atoms being less than or equal to 0.32 nanometers, and the distance between the two aluminum single atoms being less than or equal to 0.26 nanometers. More preferably, the distance between the two iron single atoms is 0.19 to 0.32 nm, and the distance between the two aluminum single atoms is 0.16 to 0.26 nm.
[0008] Preferably, the conductive substrate is a nitrogen-doped carbon material.
[0009] Preferably, the diatomic iron or diatomic aluminum accounts for more than 70% of all atomic sites on the conductive substrate. More preferably, the diatomic iron accounts for 72.4% of all atomic sites on the conductive substrate, and the diatomic aluminum accounts for 75% of all atomic sites.
[0010] The second aspect of the present invention provides a method for preparing the diatomic metal electrocatalyst according to any one of the first aspects, comprising the following steps:
[0011] (1) selecting one of anhydrous ferric chloride and anhydrous aluminum chloride as a metal precursor, placing the metal precursor and the conductive substrate horizontally or vertically in a heating device, and the placement position is such that the volatilized metal chloride dimer vapor can fully contact the conductive substrate;
[0012] The horizontal placement means that the metal precursor is at the upstream and the conductive substrate is at the downstream; the upstream and downstream here are defined by the movement direction of the volatilized metal chloride dimer vapor, and the volatilized metal chloride dimer vapor moves from the upstream to the downstream. The up-down placement means that the metal precursor is at the bottom and the conductive substrate is at the top;
[0013] (2) starting the heating device described in step (1) and setting it to heat-treat the metal precursor and the conductive substrate at a first temperature to volatilize and adsorb the metal chloride dimer, and after naturally cooling to room temperature, collecting the conductive substrate adsorbed with the metal chloride dimer;
[0014] (3) placing the conductive substrate adsorbed with the metal chloride dimer in step (2) under an inert or hydrogen atmosphere for heat treatment to obtain the diatomic metal electrocatalyst.
[0015] Preferably, in step (1), the conductive substrate is a nitrogen-containing, nitrogen-doped carbon material with a high specific surface area.
[0016] Preferably, in step (1), the mass ratio of the anhydrous ferric chloride to the conductive substrate is 1:10 to 5:1.
[0017] Preferably, in step (2), when the metal precursor is anhydrous ferric chloride, the first temperature is 300-500°C; when the metal precursor is anhydrous aluminum chloride, the first temperature is 180-300°C.
[0018] Preferably, in step (2), the adsorption time is 1 to 3 hours.
[0019] Preferably, in step (3), the temperature of the reduction heat treatment under the inert atmosphere is 700-900°C, and the time is 1-3 hours; the hydrogen volume concentration of the reduction heat treatment under the hydrogen atmosphere is 2-10%, the temperature is 300-600°C, and the time is 1-3 hours.
[0020] The third aspect of the present invention provides the use of the diatomic metal electrocatalyst described in any one of the first aspects in an oxygen reduction catalytic reaction.
[0021] The above technical solutions can be freely combined under the premise of no contradiction.
[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0023] (1) The present invention provides for the first time a diatomic metal electrocatalyst with high diatomic site density and good dispersion, which has excellent performance in oxygen reduction catalytic reactions. In the diatomic metal electrocatalyst of the present invention, the distance between two iron single atoms is less than or equal to 0.32 nanometers, the distance between two aluminum single atoms is less than or equal to 0.26 nanometers, and the proportion of the diatomic iron or diatomic aluminum in all atomic-level sites exceeds 70%.
[0024] (2) Based on the property that anhydrous ferric chloride (FeCl3) and anhydrous aluminum chloride (AlCl3) sublimate in the form of metal chloride dimers within a certain temperature range, the present invention uses a nitrogen-doped carbon conductive substrate (NC) to adsorb iron chloride dimers (Fe2Cl6) and aluminum chloride dimers (Al2Cl6) respectively. The adsorbed sample is then subjected to high-temperature heat treatment in an inert / hydrogen atmosphere to remove chlorine ligands, strengthen the interaction between the metal and the carrier, and further adjust the coordination environment of the metal iron diatoms or metal aluminum diatoms, and finally obtain a diatomic metal electrocatalyst (Fe2 / NC, Al2 / NC). The method of the present invention can achieve a high proportion, stable, and uniform dispersion of metal diatoms on the carrier.
[0025] The Fe2, Al2 diatomic metal electrocatalyst synthesis process provided by the present invention is simple to operate and has a short preparation cycle. The metal precursors used are non-precious metal salts - iron salts / aluminum salts, which have the advantage of low cost.
[0026] (3) The present invention uses the electrocatalytic oxygen reduction reaction as a probe reaction to study the catalytic excellence of the diatomic catalyst. Compared with single-atom metal electrocatalysts, the diatomic metal electrocatalysts prepared by the present invention exhibit better electrochemical oxygen reduction performance. Specifically, when the Fe2 / NC electrocatalyst catalyzes the four-electron oxygen reduction reaction, the half-wave potential can reach 0.887V vs.RHE, which is much higher than the half-wave potential of the Fe1 / NC electrocatalyst of 0.831V vs.RHE, and even better than the half-wave potential of the commercial 20wt% Pt / C of 0.871V vs.RHE. In addition, the Fe2 / NC electrocatalyst exhibits better stability than the commercial 20wt% Pt / C. After 5000 potential cycles in an alkaline environment, its half-wave potential only decays by 5mV, while the half-wave potential of Pt / C decays by nearly 30mV. When the Al2 / NC electrocatalyst catalyzes the two-electron oxygen reduction reaction, it exhibits outstanding H2O2 selectivity, up to 87%. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the X-ray diffraction pattern of the Fe2 / NC electrocatalyst prepared in the example;
[0028] Figure 2 Element mapping diagram of C and Fe in the Fe2 / NC electrocatalyst prepared in Example 2;
[0029] Figure 3 This is a spherical aberration-corrected annular dark-field phase scanning transmission electron microscopy image of the Fe2 / NC electrocatalyst prepared in Example 2;
[0030] Figure 4 is a transmission electron microscopy image of the Fe2 / NC electrocatalyst prepared in Example 3;
[0031] Figure 5 is a high-resolution transmission electron microscopy image of the Fe2 / NC electrocatalyst prepared in Example 4;
[0032] Figure 6 Element mapping diagram of C, N, and Fe in the Fe2 / NC electrocatalyst prepared in Example 4;
[0033] Figure 7 is a transmission electron microscopy image of the Fe2 / NC electrocatalyst prepared in Example 5;
[0034] Figure 8 is a transmission electron microscopy image of the Fe2 / NC electrocatalyst prepared in Example 6;
[0035] Fig. 9 Element mapping diagram of C, N, and Al in the Al2 / NC electrocatalyst prepared in Example 8;
[0036] Fig.10 This is a spherical aberration-corrected annular dark-field phase scanning transmission electron microscopy image of the Al2 / NC electrocatalyst prepared in Example 8;
[0037] Fig.11 is the X-ray diffraction pattern of the Al2 / NC electrocatalyst prepared in Example 9;
[0038] Fig.12 is a high-resolution transmission electron microscopy image of the Al2 / NC electrocatalyst prepared in Example 9;
[0039] Fig.13 This is a spherical aberration-corrected annular dark-field phase scanning transmission electron microscopy image of the Fe1 / NC electrocatalyst prepared in Comparative Example 1;
[0040] Fig.14 The oxygen reduction linear voltammetry curves of the Fe2 / NC electrocatalyst prepared in Examples 4 and 7, the Fe1 / NC electrocatalyst prepared in Comparative Example 1, and commercial 20wt% Pt / C in an oxygen-saturated 0.1M KOH electrolyte;
[0041] Fig.15 Linear voltammetric curves of the Fe2 / NC electrocatalyst prepared in Example 4 and commercial 20 wt% Pt / C after 5000 potential cycles in oxygen-saturated 0.1M KOH electrolyte.
[0042] Fig.16 H2O2 selectivity diagram of the Al2 / NC electrocatalyst and the corresponding NC substrate prepared in Examples 8 and 9 in an oxygen-saturated 0.1M KOH electrolyte; DETAILED DESCRIPTION
[0043] The present invention is further described below by way of examples, but is not limited to these examples. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions and conditions described in the manual, or under conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified. The raw materials required in the following examples and comparative examples are all commercially available.
[0044] Example 1
[0045] A method for preparing a diatomic ferroelectric catalyst comprises the following steps:
[0046] (1) Volatilization and adsorption process of iron chloride dimer (Fe2Cl6):
[0047] Take 100 mg of nitrogen-doped carbon material (NC) and 10 mg of anhydrous FeCl3, and put them into two porcelain boats respectively; then place the two porcelain boats in a tube furnace, and according to the direction of the airflow in the tube furnace, place the porcelain boat containing anhydrous FeCl3 in the upstream position, and the porcelain boat containing NC in the downstream position, and stick the two porcelain boats together; set the furnace temperature to 400 ° C, keep it warm for 3 hours, and after naturally cooling to room temperature, collect the Fe2Cl6 / NC primary product in the porcelain boat originally containing NC;
[0048] (2) Heat treatment process of Fe2Cl6 / NC primary product:
[0049] The Fe2Cl6 / NC primary product is placed in a tubular furnace and heat treated under an inert atmosphere; the furnace temperature is set to 700°C and kept warm for 1 hour. After naturally cooling to room temperature, a diatomic ferroelectric catalyst, namely Fe2 / NC, is obtained.
[0050] Figure 1 The X-ray diffraction pattern of the Fe2 / NC electrocatalyst prepared in Example 1 contains only the diffraction peak of graphitized carbon, and does not contain the diffraction peak of iron species, indicating that Fe is not aggregated into larger nanoparticles on the NC substrate.
[0051] Example 2
[0052] A method for preparing a diatomic ferroelectric catalyst comprises the following steps:
[0053] (1) Volatilization and adsorption process of iron chloride dimer (Fe2Cl6):
[0054] Take 50 mg of nitrogen-doped carbon material (NC) and 100 mg of anhydrous FeCl3, and put them into two porcelain boats respectively; then place the two porcelain boats in a tube furnace, and according to the direction of the airflow in the tube furnace, place the porcelain boat containing anhydrous FeCl3 in the upstream position, and the porcelain boat containing NC in the downstream position, and stick the two porcelain boats together; set the furnace temperature to 400 ° C, keep it warm for 3 hours, and after naturally cooling to room temperature, collect the Fe2Cl6 / NC primary product in the porcelain boat originally containing NC;
[0055] (2) Heat treatment process of Fe2Cl6 / NC primary product:
[0056] The Fe2Cl6 / NC primary product is placed in a tubular furnace and heat treated under an inert atmosphere; the furnace temperature is set to 900°C and kept warm for 3 hours. After naturally cooling to room temperature, a diatomic ferroelectric catalyst, namely Fe2 / NC, is obtained.
[0057] Figure 2 This is the element mapping diagram of C and Fe in the Fe2 / NC electrocatalyst prepared in Example 2. It can be seen from the figure that the C and Fe elements are evenly distributed on the NC substrate.
[0058] Figure 3 The spherical aberration-corrected annular dark field phase scanning transmission electron micrograph of the Fe2 / NC electrocatalyst prepared in Example 2, in which pairs of iron atoms are marked with white solid circles (the brighter points in circles A and B are two iron atoms superimposed on each other), totaling 21 pairs, and the distance between two iron atoms is indicated in the figure, in nm. This indicates that there are iron diatoms anchored on the substrate, and the distance between two iron atoms ranges from 0.19 to 0.32 nm. In the figure, single iron atoms are marked with white dotted circles, and statistics show that iron diatoms account for as much as 72.4% of all atomic-level sites.
[0059] Example 3
[0060] A method for preparing a diatomic ferroelectric catalyst comprises the following steps:
[0061] (1) Volatilization and adsorption process of iron chloride dimer (Fe2Cl6):
[0062] Take 20 mg of nitrogen-doped carbon material (NC) and 100 mg of anhydrous FeCl3, and put them into two porcelain boats respectively; then put the above two porcelain boats in a tube furnace, and according to the direction of the airflow in the tube furnace, put the porcelain boat containing anhydrous FeCl3 in the upstream position, and the porcelain boat containing NC in the downstream position, and stick the two porcelain boats together; set the furnace temperature to 300 ° C, keep it warm for 1 hour, and after naturally cooling to room temperature, collect the Fe2Cl6 / NC primary product in the porcelain boat originally containing NC;
[0063] (2) Heat treatment process of Fe2Cl6 / NC primary product:
[0064] The Fe2Cl6 / NC primary product is placed in a tubular furnace and heat treated in a hydrogen atmosphere; the hydrogen volume concentration is set to 2%, the furnace temperature is 300°C, and the temperature is kept for 1 hour. After naturally cooling to room temperature, a diatomic ferroelectric catalyst, namely Fe2 / NC, is obtained.
[0065] Figure 1 The X-ray diffraction pattern of the Fe2 / NC electrocatalyst prepared in Example 3 contains only the diffraction peak of graphitized carbon, but no diffraction peak of iron species, indicating that Fe is not aggregated into larger nanoparticles on the NC substrate.
[0066] Figure 4 This is a transmission electron microscopy image of the Fe2 / NC electrocatalyst prepared in Example 3. In the image, there are no obvious particles on the NC substrate, indicating that Fe is anchored on the NC substrate at the atomic scale.
[0067] Example 4
[0068] A method for preparing a diatomic ferroelectric catalyst comprises the following steps:
[0069] (1) Volatilization and adsorption process of iron chloride dimer (Fe2Cl6):
[0070] Take 50 mg of nitrogen-doped carbon material (NC) and 100 mg of anhydrous FeCl3, and put them into two porcelain boats respectively; then place the two porcelain boats in a tube furnace, and according to the direction of the airflow in the tube furnace, place the porcelain boat containing anhydrous FeCl3 in the upstream position, and the porcelain boat containing NC in the downstream position, and stick the two porcelain boats together; set the furnace temperature to 400 ° C, keep it warm for 3 hours, and after naturally cooling to room temperature, collect the Fe2Cl6 / NC primary product in the porcelain boat originally containing NC;
[0071] (2) Heat treatment process of Fe2Cl6 / NC primary product:
[0072] The Fe2Cl6 / NC primary product is placed in a tubular furnace and heat treated in a hydrogen atmosphere; the hydrogen concentration is set to 5%, the furnace temperature is 400°C, and the temperature is kept for 2 hours. After naturally cooling to room temperature, a diatomic ferroelectric catalyst, namely Fe2 / NC, is obtained.
[0073] Figure 1 The X-ray diffraction pattern of the Fe2 / NC electrocatalyst prepared in Example 4 contains only the diffraction peak of graphitized carbon, and does not contain the diffraction peak of iron species, indicating that Fe is not aggregated into larger nanoparticles on the NC substrate.
[0074] Figure 5This is a high-resolution transmission electron microscopy image of the Fe2 / NC electrocatalyst prepared in Example 4. In the image, there are no obvious particles and lattices on the NC substrate, indicating that Fe is anchored on the NC substrate at the atomic scale.
[0075] Figure 6 This is the element mapping diagram of C, N, and Fe in the Fe2 / NC electrocatalyst prepared in Example 4. It can be seen from the figure that C, N, and Fe elements are evenly distributed on the NC substrate.
[0076] Example 5
[0077] A method for preparing a diatomic ferroelectric catalyst comprises the following steps:
[0078] (1) Volatilization and adsorption process of iron chloride dimer (Fe2Cl6):
[0079] Take 50 mg of nitrogen-doped carbon material (NC) and 100 mg of anhydrous FeCl3, and put them into two porcelain boats respectively; then place the two porcelain boats in a tube furnace, and according to the direction of the airflow in the tube furnace, place the porcelain boat containing anhydrous FeCl3 in the upstream position, and the porcelain boat containing NC in the downstream position, and stick the two porcelain boats together; set the furnace temperature to 400 ° C, keep it warm for 3 hours, and after naturally cooling to room temperature, collect the Fe2Cl6 / NC primary product in the porcelain boat originally containing NC;
[0080] (2) Heat treatment process of Fe2Cl6 / NC primary product:
[0081] The Fe2Cl6 / NC primary product is placed in a tubular furnace and heat treated in a hydrogen atmosphere; the hydrogen concentration is set to 10%, the furnace temperature is 400°C, and the temperature is kept for 2 hours. After naturally cooling to room temperature, a diatomic ferroelectric catalyst, namely Fe2 / NC, is obtained.
[0082] Figure 1 The X-ray diffraction pattern of the Fe2 / NC electrocatalyst prepared in Example 5 contains only the diffraction peak of graphitized carbon, and does not contain the diffraction peak of iron species, indicating that Fe is not aggregated into larger nanoparticles on the NC substrate.
[0083] Figure 7 This is a transmission electron microscopy image of the Fe2 / NC electrocatalyst prepared in Example 5. In the image, there are no obvious particles on the NC substrate, indicating that Fe is anchored on the NC substrate at the atomic scale.
[0084] Example 6
[0085] A method for preparing a diatomic ferroelectric catalyst comprises the following steps:
[0086] (1) Volatilization and adsorption process of iron chloride dimer (Fe2Cl6):
[0087] Take 50 mg of nitrogen-doped carbon material (NC) and 50 mg of anhydrous FeCl3, and put them into two porcelain boats respectively; then place the two porcelain boats in a tube furnace, and according to the direction of the airflow in the tube furnace, place the porcelain boat containing anhydrous FeCl3 in the upstream position, and the porcelain boat containing NC in the downstream position, and stick the two porcelain boats together; set the furnace temperature to 500 ° C, keep it warm for 2 hours, and after naturally cooling to room temperature, collect the Fe2Cl6 / NC primary product in the porcelain boat originally containing NC;
[0088] (2) Heat treatment process of Fe2Cl6 / NC primary product:
[0089] The Fe2Cl6 / NC primary product is placed in a tubular furnace and heat treated in a hydrogen atmosphere; the hydrogen concentration is set to 5%, the furnace temperature is set to 600°C, and the temperature is kept for 3 hours. After naturally cooling to room temperature, a diatomic ferroelectric catalyst, namely Fe2 / NC, is obtained.
[0090] Figure 1 This is the X-ray diffraction pattern of the Fe2 / NC electrocatalyst prepared in Example 6. The pattern contains only the diffraction peak of graphitized carbon, but no diffraction peak of iron species, indicating that Fe is not aggregated into larger nanoparticles on the NC substrate.
[0091] Figure 8 This is a transmission electron microscopy image of the Fe2 / NC electrocatalyst prepared in Example 6. In the image, there are no obvious particles on the NC substrate, indicating that Fe is anchored on the NC substrate at the atomic scale.
[0092] Example 7
[0093] A method for preparing a diatomic ferroelectric catalyst comprises the following steps:
[0094] (1) Volatilization and adsorption process of iron chloride dimer (Fe2Cl6):
[0095] Take 50 mg of nitrogen-doped carbon material (NC) and 100 mg of anhydrous FeCl3, and place them on a carbon cloth and a porcelain boat respectively; place the carbon cloth with NC on a porcelain boat with anhydrous FeCl3, and cover the carbon cloth with another porcelain boat, then place the carbon cloth and porcelain boat in a muffle furnace; set the furnace temperature to 400 ° C, keep it warm for 1 hour, and collect the Fe2Cl6 / NC primary product on the carbon cloth after it is naturally cooled to room temperature;
[0096] (2) Heat treatment process of Fe2Cl6 / NC primary product:
[0097] The Fe2Cl6 / NC primary product is placed in a tubular furnace and heat treated under an inert atmosphere; the furnace temperature is set to 900°C and kept warm for 2 hours. After naturally cooling to room temperature, a diatomic ferroelectric catalyst, namely Fe2 / NC, is obtained.
[0098] Figure 1 The X-ray diffraction pattern of the Fe2 / NC electrocatalyst prepared in Example 7 contains only the diffraction peak of graphitized carbon, and does not contain the diffraction peak of iron species, indicating that Fe is not aggregated into larger nanoparticles on the NC substrate.
[0099] Example 8
[0100] A method for preparing a diatomic aluminum electrocatalyst comprises the following steps:
[0101] (1) Volatilization and adsorption process of aluminum chloride dimer (Al2Cl6):
[0102] Take 50 mg of nitrogen-doped carbon material (NC) and 100 mg of anhydrous AlCl3, and put them into two porcelain boats respectively; then place the two porcelain boats in a tube furnace, and according to the direction of the airflow in the tube furnace, place the porcelain boat containing anhydrous AlCl3 in the upstream position, and the porcelain boat containing NC in the downstream position, and stick the two porcelain boats together; set the furnace temperature to 180°C, keep it warm for 2 hours, and after naturally cooling to room temperature, collect the Al2Cl6 / NC primary product in the porcelain boat originally containing NC;
[0103] (2) Heat treatment process of Al2Cl6 / NC primary product:
[0104] The Al2Cl6 / NC primary product is placed in a tubular furnace and heat treated in a hydrogen atmosphere; the hydrogen concentration is set to 5%, the furnace temperature is 400°C, and the temperature is kept for 2 hours. After naturally cooling to room temperature, a diatomic aluminum electrocatalyst, namely Al2 / NC, is obtained.
[0105] Fig. 9 This is the element mapping diagram of C, N, and Al in the Al2 / NC electrocatalyst prepared in Example 8. It can be seen from the figure that C, N, and Al elements are evenly distributed on the NC substrate.
[0106] Fig.10 This is a spherical aberration-corrected annular dark field phase scanning transmission electron micrograph of the Al2 / NC electrocatalyst prepared in Example 8. Pairs of aluminum atoms are marked with white solid circles, totaling 12 pairs, and the distance between aluminum diatoms is indicated in the figure in nm. This indicates that there are aluminum diatoms anchored on the substrate, and the distance between aluminum diatoms ranges from 0.16 to 0.26 nm. Single aluminum atoms are marked with white dotted circles in the figure, and statistics show that aluminum diatoms account for up to 75% of all atomic-level sites.
[0107] Example 9
[0108] A method for preparing a diatomic aluminum electrocatalyst comprises the following steps:
[0109] (1) Volatilization and adsorption process of aluminum chloride dimer (Al2Cl6):
[0110] Take 50 mg of nitrogen-doped carbon material (NC) and 100 mg of anhydrous AlCl3, and put them into two porcelain boats respectively; then place the two porcelain boats in a tube furnace, and according to the direction of the airflow in the tube furnace, place the porcelain boat containing anhydrous AlCl3 in the upstream position, and the porcelain boat containing NC in the downstream position, and stick the two porcelain boats together; set the furnace temperature to 300 ° C, keep it warm for 2 hours, and after naturally cooling to room temperature, collect the Al2Cl6 / NC primary product in the porcelain boat originally containing NC;
[0111] (2) Heat treatment process of Al2Cl6 / NC primary product:
[0112] The Al2Cl6 / NC primary product is placed in a tubular furnace and heat treated in a hydrogen atmosphere; the hydrogen concentration is set to 5%, the furnace temperature is 400°C, and the temperature is kept for 2 hours. After naturally cooling to room temperature, a diatomic aluminum electrocatalyst, namely Al2 / NC, is obtained.
[0113] Fig.11 The X-ray diffraction pattern of the Al2 / NC electrocatalyst and the NC substrate prepared in Example 9, in which Al2 / NC has a similar spectrum to NC, contains only the diffraction peak of graphitized carbon, and does not contain the diffraction peak of aluminum species, indicating that Al is not aggregated into larger nanoparticles on the NC substrate.
[0114] Fig.12 This is a high-resolution transmission electron microscopy image of the Al2 / NC electrocatalyst prepared in Example 9. In the image, there are no obvious particles and lattices on the NC substrate, indicating that Al is anchored on the NC substrate at the atomic scale.
[0115] Comparative Example 1
[0116] The preparation method of single-atom iron electrocatalyst adopts the traditional impregnation method, which includes the following steps:
[0117] 100 mg of nitrogen-doped carbon material (NC) was placed in 16 ml of deionized water and ultrasonicated for 30 minutes to obtain a uniform NC dispersion; 9 mg of anhydrous FeCl3 was dissolved in 4 ml of deionized water to obtain a FeCl3 solution; the FeCl3 solution was added dropwise to the NC dispersion and stirred at room temperature for 12 hours; after stirring, the obtained sample was washed with deionized water and anhydrous ethanol for multiple times, and then placed in a 60°C oven to dry for 12 hours; the dried sample was placed in a tubular furnace and heat treated in a hydrogen atmosphere according to step (2) of Example 4; the hydrogen concentration was set to 5%, the furnace temperature was set to 400°C, and the mixture was kept warm for 2 hours. After naturally cooling to room temperature, a single-atom ferroelectric catalyst, namely Fe1 / NC, was obtained.
[0118] Fig.13 This is a spherical aberration-corrected annular dark-field phase scanning transmission electron microscopy image of the Fe1 / NC electrocatalyst prepared in Comparative Example 1. It can be seen from the figure that the iron in the Fe1 / NC electrocatalyst exists in the form of single iron atoms, where the single iron atoms are marked with white circles.
[0119] Application Example 1
[0120] Electrochemical ORR (oxygen reduction) performance tests were performed on the Fe2 / NC electrocatalysts prepared in Examples 4 and 7, the Fe1 / NC electrocatalyst prepared in Comparative Example 1, and a commercial 20 wt% Pt / C catalyst.
[0121] (1) Preparation of working electrode:
[0122] Accurately weigh 5.0 mg of the catalyst to be tested, add 980 μL of ethanol and 20 μL of 5% Nafion solution (perfluorosulfonic acid polymer solution), and ultrasonically disperse for 2 hours to obtain a catalyst dispersion. Then take 20 μL of the catalyst dispersion and drop it onto the disk electrode, and after natural drying, obtain a working electrode.
[0123] (2) Performance testing methods:
[0124] The electrochemical ORR test adopts a three-electrode reaction system, in which a stone mill rod is used as a counter electrode, a calomel electrode is used as a reference electrode, and a disk electrode coated with the catalyst to be tested is used as a working electrode. Cyclic voltammetry and linear sweep voltammetry tests are performed in an oxygen-saturated 0.1 M KOH electrolyte.
[0125] Fig.14 The ORR linear voltammograms of the Fe2 / NC electrocatalyst prepared in Examples 4 and 7, the Fe1 / NC electrocatalyst prepared in Comparative Example 1, and the commercial 20wt% Pt / C catalyst in an oxygen-saturated 0.1M KOH electrolyte are shown in the figure. It can be seen from the figure that the half-wave potentials of the Fe2 / NC electrocatalyst are 0.858V vs.RHE and 0.887V vs.RHE, respectively, which are much higher than the half-wave potential of the Fe1 / NC catalyst of 0.831V vs.RHE, and are close to or higher than the half-wave potential of the commercial 20wt% Pt / C catalyst of 0.871Vvs.RHE, indicating that the prepared Fe2 / NC electrocatalyst has an outstanding 4e - ORR catalytic activity.
[0126] Fig.15The ORR linear voltammetric curve of the Fe2 / NC electrocatalyst prepared in Example 4 and the commercial 20wt% Pt / C catalyst after 5000 potential cycles in an oxygen-saturated 0.1M KOH electrolyte. It can be seen from the figure that after 5000 potential cycles, the half-wave potential of the Fe2 / NC electrocatalyst decays by only 5mV, which is less than the half-wave potential decay value of the commercial 20wt% Pt / C catalyst of 30mV, indicating that the prepared Fe2 / NC electrocatalyst has a better 4e - ORR catalytic stability.
[0127] Application Example 2
[0128] The electrochemical ORR performance of the Al2 / NC electrocatalysts prepared in Examples 8 and 9 and the corresponding NC substrates was tested.
[0129] (1) Preparation of working electrode:
[0130] Accurately weigh 5.0 mg of the catalyst to be tested, add 980 μL of ethanol and 20 μL of 5% Nafion solution (perfluorosulfonic acid polymer solution), and ultrasonically disperse for 2 hours to obtain a catalyst dispersion. Then take 20 μL of the catalyst dispersion and drop it onto the ring-disk electrode, and after natural drying, obtain a working electrode.
[0131] (2) Performance testing methods:
[0132] The electrochemical ORR test used a three-electrode reaction system, in which a stone mill rod was used as a counter electrode, a calomel electrode was used as a reference electrode, and a ring-disk electrode coated with the catalyst to be tested was used as a working electrode. Cyclic voltammetry and linear sweep voltammetry tests were performed in an oxygen-saturated 0.1 M KOH electrolyte.
[0133] Fig.16 Figure 2 is the H2O2 selectivity diagram of the Al2 / NC electrocatalyst prepared in Examples 8 and 9 and the corresponding NC substrate in an oxygen-saturated 0.1M KOH electrolyte. It can be seen from the figure that the H2O2 selectivity of the Al2 / NC electrocatalyst is between 73% and 87%, which is much higher than the H2O2 selectivity of the NC substrate (less than 50%), indicating that the diatomic Al site in the prepared Al2 / NC electrocatalyst has a catalytic 2e - ORR effect, and showed an outstanding 2e - ORR selectivity.
Claims
1. A diatomic metal electrocatalyst, characterized in that: The diatomic metal electrocatalyst includes: a conductive substrate, diatomic iron or diatomic aluminum loaded on the conductive substrate, the diatomic iron is two iron single atoms, the diatomic aluminum is two aluminum single atoms, and the distance between the two iron single atoms is less than or equal to 0.32 nanometers, and the distance between the two aluminum single atoms is less than or equal to 0.26 nanometers.
2. The diatomic metal electrocatalyst according to claim 1, characterized in that The conductive substrate is a nitrogen-doped carbon material.
3. The diatomic metal electrocatalyst according to claim 1, characterized in that The diatomic iron or the diatomic aluminum occupies more than 70% of all atomic-scale sites on the conductive substrate.
4. The method for preparing a diatomic metal electrocatalyst according to any one of claims 1 to 3, characterized in that: The steps include: (1) selecting one of anhydrous ferric chloride and anhydrous aluminum chloride as a metal precursor, placing the metal precursor and the conductive substrate horizontally or vertically in a heating device, and the placement position is such that the volatilized metal chloride dimer vapor can contact the conductive substrate; The horizontal placement means that the metal precursor is at the upstream and the conductive substrate is at the downstream; the up-and-down placement means that the metal precursor is at the bottom and the conductive substrate is at the top; (2) starting the heating device described in step (1), heat-treating the metal precursor and the conductive substrate at a first temperature to volatilize and adsorb the metal chloride dimer, and collecting the conductive substrate adsorbed with the metal chloride dimer after naturally cooling to room temperature; (3) placing the conductive substrate adsorbed with the metal chloride dimer in step (2) under an inert or hydrogen atmosphere for heat treatment to obtain the diatomic metal electrocatalyst.
5. The preparation method according to claim 4, characterized in that: In step (1), the conductive substrate is a nitrogen-doped carbon material.
6. The preparation method according to claim 4, characterized in that: In step (1), the mass ratio of the metal precursor to the conductive substrate is 1:10 to 5:
1.
7. The preparation method according to claim 4, characterized in that: In step (2), when the metal precursor is anhydrous ferric chloride, the first temperature is 300-500°C; when the metal precursor is anhydrous aluminum chloride, the first temperature is 180-300°C.
8. The preparation method according to claim 4, characterized in that: In step (2), the adsorption time is 1 to 3 hours.
9. The preparation method according to claim 4, characterized in that: In step (3), the temperature of the heat treatment under the inert atmosphere is 700-900° C., and the time is 1-3 hours; the hydrogen volume concentration of the heat treatment under the hydrogen atmosphere is 2-10%, the temperature is 300-600° C., and the time is 1-3 hours.
10. Use of the diatomic metal electrocatalyst according to any one of claims 1 to 3 in oxygen reduction catalytic reaction.
Citation Information
Patent Citations
Carbon supported transition metal atom pair electrocatalyst and preparation method and application thereof
CN109686988A
Nitrogen-doped carbon-supported monoatomic oxygen reduction catalyst and preparation method thereof
CN109841854A
Ni-Fe diatomic electrocatalyst, and preparation method and application thereof
CN111185176A
FeTe diatomic catalyst and preparation method thereof
CN116344845A
Preparation method and application of iron-based heteronuclear diatomic active site oxygen reduction catalyst
CN119050385A